The Problems in Speaking for English Department Student in STKIP BUDIDAYA – BINJAI - Ayu Indari (STKIP Budidaya Binjai, 2020)
This paper is purposed to find out the problems in speaking skills for English department student in STKIP Budidaya – Binjai. The speaking skill is the last position to cover up the four skills in English because speaking is the improving your ability to use four skills in English. Speaking needs some stimulation to attract the students speaks their ideas, opinion, or comments about something. The sample of the study is the third students in English department student, it is around 28 students. The data are collected through document by sound recording. The data analyzed by using the technique of analyze data. The result of the study is that it concludes that first question “What is the problem of speaking?” 10 students (35,71%) respond less of confident and 10 students (35,71%) respond less of vocabulary. The second question “How the ways do you practice your speaking skill?” 10 students (35,71%) respond watching movie. The third question “Do you agree that speaking is the most difficult to study comparing with another skills in English? And why?” 18 students (64,29%) respond yes, because it takes orally.